Influence of Clinical and Tumor Factors on Interfraction Setup Errors With Rotation Correction for Vacuum Cushion in Lung Stereotactic Body Radiation Therapy - Chen, Hua; Liu, Lingxiang; Wang, Hao; Shao, Yan; Gu, Hengle; Duan, Yanhua; Feng, Aihui; Huang, Ying; Xu, Zhiyong (Frontiers in Oncology, 2021)
Purpose: To explore influence of clinical and tumor factors over interfraction setup errors with rotation correction for non-small cell lung cancer (NSCLC) stereotactic body radiation therapy (SBRT) patients immobilized in vacuum cushion (VC) to better understand whether patient re-setup could further be optimized with these parameters. Materials and methods: This retrospective study was conducted on 142 NSCLC patients treated with SBRT between November 2017 to July 2019 in the local institute. Translation and rotation setup errors were analyzed in 732 cone-beam computed tomography (CBCT) scans before treatment. Differences between groups were analyzed using independent sample t-test. Logistic regression test was used to analyze possible correlations between patient re-setup and clinical as well as tumor factors. Results: Mean setup errors were the largest in anterior-posterior (AP) direction (3.2 ± 2.4 mm) compared with superior-inferior (SI) (2.8 ± 2.1 mm) and left-right (LR) (2.5 ± 2.0 mm) directions. The mean values were similar in pitch, roll and rtn directions. 83.7%, 90.3% and 86.6% of fractions satisfied setup error tolerance limits in AP, SI and LR directions, whereas 95% of fractions had rotation setup errors of less than 2° in the pitch, roll or rtn directions. Setup errors were significantly different in the LR direction when age, body mass index (BMI) and “right vs. left” location parameters were divided into groups. Both univariate and multivariable model analyses showed that age (p = 0.006) and BMI (p = 0.002) were associated with patient re-setup. Conclusions: Age and BMI, as clinical factors, significantly influenced patient re-setup in the current study, whereas all other clinical and tumor factors were not correlated with patient re-setup. The current study recommends that more attention be paid to setup for elderly patients and patients with larger BMI when immobilized using VC, especially in the left-right direction.